Peranan Tata Kelola sebagai Pemoderasi atas Pengaruh Manajemen Laba terhadap Efisiensi Investasi - Yapono, Dania Amani; Khomsatun, Siti (Jurnal Dinamika Akuntansi dan Bisnis, 2018)
The purpose of this study is to analyze the effect of earnings management on corporate investment efficiency and to examine whether the corporate governance mechanism such as institutional ownership, the independence of the board of commissioners and the expertise of the board of commissioners be able to moderating those effects. The population in this study is manufacturing companies listed on the Indonesian Sharia Stock Index (ISSI) during 2014-2016. This study uses purposive sampling method and unbalanced panel data regression. The results of this study indicate that earnings management has a significant negative effect on investment efficiency. The institutional ownership is able to weaken the negative relationship. The independence and expertise of the board of commissioners has no effect to moderate the negative relationship between earnings management and investment efficiency.